Autorreferencia y estilo terapéutico: su intersección en la formación de terapeutas sistémicos (2008)
This paper refers the mode how in the Auto-reference and therapeutic style seminary of the Magister in psychology and the family program in the Santo Tomas University, contribute to the therapist education in a systemic paradigm, through a life experience that refers to "self" in its intersubjective dimension. It is made through complex human interchanges contextualized within psico-social-anthropological relational dynamics which give frame to conversational, reflective and metaobservation processes, in the emergency of meanings directly associate to the knowledge in the formation and in the therapy. The final aim is to construct a knowledge that is put to the service of the transformation of the human suffering through therapist as a conscious manager of the change from an ethical position. In this way is insisted on the experiential components required by the psychotherapists to make its transit towards the second order epistemology proposed by Von Foerster through an exercise based on the self-reference. Key words: self-reference, therapeutic style, therapist.